CHANGES IN MANAGEMENT AS AN INSTRUMENT OF EDUCATIONAL INTERVENTION - Paun, Mihaela-Gabriela (European Scientific Journal, ESJ, 2013)
In this study, based on the fact that training is an important component of the educational sector both for undergraduate and graduate students, the necessity of knowledge concept as a process of change is imposed. This argument is based on the models which serves as the centre of the change: professional skills of the trainer – the axes of V. Hall, N. Cromey-Hawke and D. Oldroyd: time, content, meetings; Kurt Lewin’s model are in two dimensions: knowledge of self, lack of sufficient knowledge of self and self-concern, lack of self-absorption; but the underlying methodology entails the development and organization of training programmes in order to stimulate the learner to adapt to new existential contexts. In conclusion, we noted that the support of the learner’s motivation to continue the auto-training process is closely linked to the trainee’s ability to identify the most appropriate methods required as the conditions for training. Thus, at the same time, they continued to examine the cycle of M. Pedler, J. G. Burgoyne and T. Boydell. Hence, the advantages and disadvantages of the various types of training included in the training programmes as methods, and a number of conditions which followed, lead to an increase in the efficiency of the formation and the development of mutual trust between the trainers and the trainees